Job Stress and Nurses Well-Being: Prayer and Age as Moderators - Achour, Meguellati; Azmi, Ilhaamie Abdul Ghani; Isahak, Marzuki; Nor, Mohd Roslan Mohd; Mohd Yusoff, Mohd Yakub @ Zulkifli (Springer, 2019)
There is increasing popularity among researchers, scholars, and policymakers concerning the efficacy of prayer as a coping strategy for job stress. This study examines the moderating effects of prayer and age on the relationship between job stress and nurses’ well-being in UMMC. Three hundred (300) Muslim nursing staff working at the University of Malaya Medical Centre were sampled. Data were collected via questionnaires. The findings of this study show that the effect of job stress on well-being is significant for nurses and that prayer of nurses contributed to alleviating job stress and enhancing well-being. This study is limited to nurses in one public hospital in a developing country. Thus, it would be more interesting if the study could be extended to other public and private institutions in a Muslim country, and a comparison could be done between other religions as well. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.